Effectiveness of Online Focus Group Discussion on English Reading Skill: A Classroom Action Research During Pandemic Covid-19 (Pascasarjana Universitas Negeri Makassar, 2022)
English as international language is being taught at school, establishing a variety of teaching and learning method in improving the four language skills. Focus Group Discussion (FGD) is deemed to be suited in improving the aforementioned skills providing discussion as its main benefit in English learning, especially in Reading skill. This research implemented CAR (Classroom Action Research) by employing Focused Group Discussion as the research method. The research process is carried out directly through online meeting as required during the pandemic Covid 19 situation. The research subjects are students of MTs Surya Buana School in Malang who are willing to take a part in this research as the research participants. This research employed interview and questionnaire techniques conducted in one pre meeting and two cycles of Classroom Action Research. The instruments used by authors to collect data were pre-test and posttest, observation sheet and interview guide. Based on the collection of data from this classroom action research, the authors concluded that the students 'reading ability by applying the focus group discussion method was very helpful and also can be a good method to improve students' reading skill. Focus group discussions not only improve students 'reading skill but also increase students' self-confidence. This method also enhances communication and interaction with other students. The research implied that online FGD is effective to enhance reading skill.